Dynamic Economic Effects of EU Membership for Post Socialist Countries of Central and Eastern Europe - Bilenko, Yuriy (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
This study of the dynamic effects of regional integration within the EU focuses on the achievements of the traditional and new schools of economic growth. We analyzed the specific dynamic effects of integration of Central and Eastern Europe countries into the European Union in the medium term according to theoretical model of R. Baldwin and A. Venables, taking into account five-year periods before (1999-2003) and after (2004-2008) accession. In the study, we chose the following countries of Central and Eastern Europe: Slovakia, Poland, Hungary, the Czech Republic, Latvia, Lithuania, Estonia and Slovenia. This research is one of the first attempts to assess dynamic economic effects ex post and to test theoretical models of economic integration on examples that took place ex ante EU enlargement in 2004. The processes of accumulation of physical and human capital are the basis of dynamic economic effects of European integration of the countries of Central and Eastern Europe and long-term sustainable growth. The results we obtained can be regarded as proof that these countries have developed according to the AK model of endogenous growth, which involves constant or increasing returns on physical and human capital. In all CEE countries, the growth rate of physical capital significantly increased throughout the EU membership period, as did the share of employment in high-tech industry sectors. Our study confirmed that the relatively capital-intensive sector in member countries gained developmental momentum in connection with the expansion of the market, which will cause increased demand for capital, and unification led to investment-oriented economic growth that is stimulated by changes in the production structure of the trade sector.
Keywords: Unia Euroopejska; skutki gospodarcze; kraje postkomunistyczne; Europa Środkowo-Wschodnia